2021
DOI: 10.1021/acsami.0c18490
|View full text |Cite
|
Sign up to set email alerts
|

Chain Conformation Control of Fluorene-Benzothiadiazole Copolymer Light-Emitting Diode Efficiency and Lifetime

Abstract: The β-phase, in which the intermonomer torsion angle of a fraction of chain segments approaches ∼180°, is an intriguing conformational microstructure of the widely studied light-emitting polymer poly­(9,9-dioctylfluorene) (PFO). Its generation can in turn be used to significantly improve the performance of PFO emission-layer-based light-emitting diodes (LEDs). Here, we report the generation of β-phase chain segments in a copolymer, 90F8:10BT, containing 90% 9,9-dioctylfluorene (F8) and 10% 2,1,3-benzothiadiazo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…High-efficiency deep-blue emission is one of the primary advantages of polyfluorene-based LCPs. [17][18][19] However, owing to the nature of the wide band gap, devices' color purity is susceptible to internal defects induced by interchain aggregates or device operation. [20][21][22] This is why some reported strategies for stretchable devices inevitably manifested or aggravated defect emission in the electroluminescence (EL) spectra of polyfluorene-based blue light-emitting diodes.…”
Section: Introductionmentioning
confidence: 99%
“…High-efficiency deep-blue emission is one of the primary advantages of polyfluorene-based LCPs. [17][18][19] However, owing to the nature of the wide band gap, devices' color purity is susceptible to internal defects induced by interchain aggregates or device operation. [20][21][22] This is why some reported strategies for stretchable devices inevitably manifested or aggravated defect emission in the electroluminescence (EL) spectra of polyfluorene-based blue light-emitting diodes.…”
Section: Introductionmentioning
confidence: 99%
“…The loading range selected was guided by prior studies 16,17 that showed successful β-phase formation for 9,9-dioctylfluorene-based copolymers in the presence of bulky co-monomer units for fractions below about 20% and with an eye to avoiding a switch from co-monomer-modulated 9,9-dioctylfluorene emission to comonomer-dominated emission. The general study of absorption and photoluminescence (PL) emission for (100-X)F8:XPyTPA-Pt(acac) polymer films with different PyTPA-Pt(acac) fractions and 9,9-dioctylfluorene conformations (see Supporting Information Figure S1 to S3 for full data sets) was followed by a more detailed study of triplet energy transfer as a function of temperature and conformation for the 5% loading, 95F8:5PyTPA-Pt(acac) copolymer (Figure 1B).…”
Section: Introductionmentioning
confidence: 99%
“…Polyfluorenes combine high photoluminescence (PL) quantum yields, good thermal stability and good solubility in a variety of solvents. However, the PL efficiency of these organic conjugated polymers (OCPs) strongly depends on the properties and relaxation processes of the electronic excited states, which has led to considerable efforts in characterizing their behavior in solution. Moreover, the photophysical properties are strongly determined by chemical structure, molecular weight, the presence of defects, the solvent from which the polymer is processed, and chain conformation and interchromophorics. In many of these polymers, physical and/or chemical properties change as a response to external environmental stimuli, such as temperature, pH, electrolyte, light, electricity, magnetic field, etc. , In OCPs, the main deactivation excited-state pathway involves optical excitations that migrate along the polymer chain, or between different chains, executing a random walk inside the broadened conjugation length, and therefore, different excitation energies. , However, in polyfluorenes an additional competitive deactivation pathway, competitive with intrachain electronic energy transfer, is presented and involves conformational relaxation. ,, …”
Section: Introductionmentioning
confidence: 99%